วาทกรรม อำนาจ และการสื่อสารวาทกรรมภิกษุณีเถรวาทของไทย - พงษ์พันธุ์ กีรติวศิน (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This research aims to analyze and to explain discourses and communication of Theravada bhikkhuni discourses, and to criticize power relate to discourses under Michel Foucault’s discourse concept. This research employs critical discourse analysis method, using documents from The National Archives of Thailand during the year 1928 – 1929, books, printed media, and in-depth interview with 7 bhikkhunis from nationwide. The finding of the study reveals that there are at least two attempts to restore Theravada bhikkhuni ordination in Thailand. The first attempt was recorded in 1928, initiated by a former governor, Narin Phasit. The attempt failed but ignited the dispute about the legitimacy of the revival of Theravada bhikkhuni. The controversy erupts fervently again in 2001 when Chatsumarn Kabilsingh went for her ordination in Sri Lanka and claims for being the first Theravada bhikkhuni of Thailand. The dispute of the two attempts constructed knowledge of Buddhism, power of the state and traditions. These knowledge practice through communication strategies; explanation, argument and reproach, power enforcement, organizational and institutional power, violence, obstinacy. These strategies communicate implement by using mass media, social media, law enforcement, academic activities, and ritual practices and social contribution activities of bhikkhunis.